VIABILIDAD TÉCNICA PARA LA PRODUCCIÓN DE ADOQUINES UTILIZANDO RELAVES MINEROS DE LA CONCESIÓN MINERA JOYA DEL ORIENTE II, CÓDIGO 501381, UBICADA EN LA PARROQUIA LOS ENCUENTROS, CANTÓN YANTZAZA, PROVINCIA ZAMORA CHINCHIPE - Ordóñez Mendoza, Katy Carina (2025)
Currently, the main challenge faced by small and medium mining companies with an environmental approach is the management of tailings due to the risk of contamination and alteration of the ecosystem, these mining wastes are stored in dams where they remain indefinitely. The purpose of this research is to evaluate the technical feasibility of producing paving stones using tailings from the Joya del Oriente II mining concession, code 501381. We worked with 5 tailings samples and characterized the physical, chemical and mineralogical properties of the tailings to determine their properties as aggregate. The physical characteristics of the tailings were alkaline pH, a density of 2.5 g/cm3 to 4 g/cm3, a fine grain size due to a silty grained soil. The mineralogical characterization indicated that the predominant mineral is quartz, with mineralogical composition of silica with 61.62%; these minerals were detected in low percentages such as pyrite, calcite, muscovite, plagioclase. The optical emission spectroscopy analysis indicated high concentrations of lead, which is due to the epithermal type deposit of the concession. With the results of the analysis of the tailings from the Joya de Oriente mine, it was determined that it is posible produce paving stones with a dosage of 40%. subsequecy, analyzing samples of manufactured paving stones, it was obtained that these compliance with the criteria established by the INEN 3040 and INEN 1485 standards. therefore paving stones can be use in pedestrian transit areas and parking áreas.